2005
DOI: 10.1021/bi050118y
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Downhill Folding:  Guidelines for the Analysis of Equilibrium Folding Experiments on Small Proteins

Abstract: Previously, we identified the protein BBL as a downhill folder. This conclusion was based on the statistical mechanical analysis of equilibrium experiments performed in two variants of BBL, one with a fluorescent label at the N-terminus, and another one labeled at both ends. A recent report has claimed that our results are an artifact of label-induced aggregation and that BBL with no fluorescent labels and a longer N-terminal tail folds in a two-state fashion. Here, we show that singly and doubly labeled BBL d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
153
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(171 citation statements)
references
References 52 publications
18
153
0
Order By: Relevance
“…Figure 5 shows DSC thermograms for free energy surfaces with a high barrier (~ 18 kJ/mol at the midpoint, see inset), a marginal barrier (~3 kJ/mol at the midpoint, see inset), and fully downhill. The three DSC thermograms can be well fit to a chemical two-state model (continuous lines), as has been discussed before for experimental DSC data (62,65). However, comparison with the true theoretical DSC baseline reveals that the fitted "native" baseline becomes increasingly sloped and shifts to higher values (i.e.…”
Section: Manifestations Of Folding With Marginal (Or No) Barriersmentioning
confidence: 63%
See 2 more Smart Citations
“…Figure 5 shows DSC thermograms for free energy surfaces with a high barrier (~ 18 kJ/mol at the midpoint, see inset), a marginal barrier (~3 kJ/mol at the midpoint, see inset), and fully downhill. The three DSC thermograms can be well fit to a chemical two-state model (continuous lines), as has been discussed before for experimental DSC data (62,65). However, comparison with the true theoretical DSC baseline reveals that the fitted "native" baseline becomes increasingly sloped and shifts to higher values (i.e.…”
Section: Manifestations Of Folding With Marginal (Or No) Barriersmentioning
confidence: 63%
“…A typical example is the interpretation of two observed kinetic phases as an indication of a kinetically populated intermediate. Other deviations are just ignored, or blamed on experimental uncertainties (65). In principle, the marginal barrier and two-state folding regimes could be simply distinguished by measuring the free energy barrier in a DSC experiment.…”
Section: Manifestations Of Folding With Marginal (Or No) Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Those probes that switch signal at lower free energy yield lower melting temperatures. 11,[21][22][23][24][25] In the kinetic approach, the temperature is tuned to identify the appearance of probe-dependent rates and the appearance/ disappearance of nonexponential kinetics. 10,12,26,27 Generally, folding barriers ⌬G † decrease as we tune from the melting temperature T m to the temperature of maximum stability.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Fersht and coworkers (15,16) examined the structural, denaturation, and kinetic properties of PSBD homologues from E. coli [unlabeled wild-type BBL, Protein Data Bank (PDB) entry 1W4H], Bacillus stearothermophilus (E3BD F166W, PDB entry 1W4E), and Pyrobaculumaerophilum (POB Y166W L146A, PDB entry 1W4J) (17) and found that 1W4H, 1W4E, and 1W4J follow the typical two-state folding scheme. Whereas Naganathan et al (18) argued that the experimental data in ref. 15 support the global downhill folding scenario, Fersht and coworkers (16) believe that the conclusion drawn by Muñoz and coworkers was obtained by an incorrect assumption and analysis of the data in refs.…”
mentioning
confidence: 97%